Commentaires sur l’étude de Jevne - Bujold, Charles (Canadian Journal of Counselling and Psychotherapy, 2012)
Charles Bujold presents his comments on Jevne's (1981) article and treats three aspects: (1) Utilization of psychometry and information in counselling in its broadest sense; (2) the role of the educator in the training of counsellors; (3) the general practice versus specialization in the training of counsellors. Jevne exposes a certain amount of data related to the skills considered to be important for Canadian counsellors and points relating to their training. The data is based on "informed opinions" rather than on empirically verifiable knowledge which would be sufficiently consistent and convergent to be used as a frame of reference in the elaboration of policies relating to the professional preparation of future counsellors.